Sex and gender considerations in low back pain clinical practice guidelines: a scoping review - Luciana G Macedo; Tori Rathbone; Catherine Truong; Haley Haldenby; Sara Riazi; Mara Kendall; Tayler Cimek (BMJ Open Sport & Exercise Medicine)
Objective The purpose of this scoping review is to determine if and how sex and gender have been incorporated into low back pain (LBP) clinical practice guidelines (CPG), and if sex and gender terms have been used properly.Methods CPGs were searched on MEDLINE, Embase, NICE, TRIP and PEDro from 2010 to 2020. The inclusion criteria were English language, CGPs within physiotherapy scope of practice and for adult population with LBP of any type or duration. Three pairs of independent reviewers screened titles, abstracts and full texts. Guidelines were searched for sex/gender-related terms and recommendations were extracted. The AGREE II (Appraisal of Guidelines for Research and Evaluation II) was used to evaluate the quality of the CPGs.Results Thirty-six CPGs were included, of which 15 were test-positive for sex or gender terms. Only 33% (n=5) of CPGs incorporated sex or gender into diagnostic or management recommendations. Sixty percent of guidelines (n=9) only referenced sex or gender in relation to epidemiology, risk factors or prognostic data, and made no specific recommendations. Overall, there was no observable relationship between guideline quality and likeliness of integrating sex or gender terms. The majority of guidelines used sex and gender terms interchangeably, and no guidelines defined sex or gender.Conclusion CPGs did not consistently consider sex and gender differences in assessment, diagnosis or treatment of LBP. When it was considered, sex and gender terms were used interchangeably, and considerations were primarily regarding pregnancy. Researchers should consider the importance of including sex-based and/or gender-based recommendations into future LBP CPGs.